Desenvolvimento de catalisadores para reforma e oxidação combinadas do metano - Silva, Tatiana de Freitas (2009)
In this work, we studied the effects of the promoters of support (ZrO2, La2O3, CeO2, CeO2-ZrO2, CeO2-ZrO2-La2O3 and La2O3) in the nickel catalysts supported on γ-Al2O3 were studied. The supports were prepared by wet impregnation on γ- Al2O3 (Alfa Aesar) with 10% by weight of oxides of cerium, zirconium, lanthanum, ceria-zirconia, ceria-lanthanum and lanthanum-zirconium. The addition of nickel was performed by impregnation of the supports using an aqueous solution of Ni(NO3)2.6H2O (Fluka), followed by drying at 373 K for 24 hours and calcined in synthetic air (80 ml / min) at 823 K for 5 h. The samples were characterized by dispersive spectroscopy X-ray (EDX), analysis of BET, X-ray diffraction (XRD), temperature programmed reduction (TPR), temperature programmed Desorption (TPD), and temperature programmed oxidation (TPO). The catalysts were studied for steam reforming, partial oxidation and oxidative reforming of methane. For steam reforming, the catalysts that have two promoters and the catalyst NiLaAl presented the highest catalytic activities. In the partial oxidation the values of conversion of methane produced by different catalysts are similar. In the oxidative reforming the catalysts that have only one type of promoter and the catalyst NiCeLaAl, above 500 º C showed the best catalytic performance.